2009
DOI: 10.1111/j.1749-818x.2008.00102.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of Executive Control and Language Processing

Abstract: Research in executive function development has shown that children have poor control of inhibition functions, including the inhibition of prepotent responses, control of attention, and flexibility at rule‐shifting. To date, links between the development of executive function and children's language development have not been investigated explicitly. Yet, recent studies on children's sentence processing report that children tend to perseverate during sentence processing. We argue that such perseveration may be d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
65
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(75 citation statements)
references
References 147 publications
4
65
0
Order By: Relevance
“…We found that inhibition (but not shifting or updating) was a reliable predictor of syntactic performance, even after accounting for age, SES, and IQ. Our finding with respect to the inhibition-syntax relationship is consistent with previous studies that showed an association between inhibition and syntactic comprehension abilities (Choi & Trueswell, 2010;Mazuka et al, 2009;Novick et al, 2005;Woodard et al, 2016). It is notable that prior studies have also identified relationships between syntactic performance and updating (Moser et al, 2007;Roberts et al, 2007), whereas we did not.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…We found that inhibition (but not shifting or updating) was a reliable predictor of syntactic performance, even after accounting for age, SES, and IQ. Our finding with respect to the inhibition-syntax relationship is consistent with previous studies that showed an association between inhibition and syntactic comprehension abilities (Choi & Trueswell, 2010;Mazuka et al, 2009;Novick et al, 2005;Woodard et al, 2016). It is notable that prior studies have also identified relationships between syntactic performance and updating (Moser et al, 2007;Roberts et al, 2007), whereas we did not.…”
Section: Discussionsupporting
confidence: 79%
“…On the other hand, other studies have linked lexical-semantic processing with updating of working memory (Gathercole & Baddeley, 1990;Khanna & Boland, 2010;Weiland, Barata, & Yoshikawa, 2013), although it is notable that many of these studies used verbal measures of working memory (e.g., Gathercole & Baddeley, 1990;Weiland et al, 2013). Whereas some studies have also found that syntactic processing was associated with inhibition and/or shifting (Mazuka et al, 2009;Novick et al, 2005), others have linked syntactic processing with updating (Moser et al, 2007;Roberts et al, 2007). It is possible, and even likely, that different aspects of language processing (and/or different language-processing tasks) are associated with distinct EF skills.…”
Section: Ef and Language Abilitiesmentioning
confidence: 94%
See 3 more Smart Citations